The Role of Teachers and Families in Improving Motivation and Learning Outcomes of Students - Firja Ahmad; Fatimah Saguni; Rustina Rustina (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2019)
This study examines the role of teachers and families in improving motivation and learning outcomes of students. This study uses qualitative methods in the form of field research. The data are collected through observation, interviews, and documentation. Data Analysis was performed using data reduction, data presentation, and data verification. The results showed that the teachers’ roles in increasing students'learning motivation are to clarify goals, arouse students' interests through learning processes, extracurricular activities and self-development programs and create a pleasant learning atmosphere. The roles of the family are to provide attention and affection, provide guidance and advice as well as supplying students with the learning facilities they need. In improving students’ learning outcomes, teachers and families need to communicate and cooperate for instance the teacher gives the task and the family carries out supervision at home. However, the lack of family attention caused by economic problems and busyness at work resulted in the insignificance of the families’ role in increasing motivation and learning outcomes of students.